New Trends in Latin American Constitutionalism: An Overview - Legarre, Santiago (2014)
In this introduction to the issue on New Trends in Latin American Con-stitutionalism, Santiago Legarre offers his remarks at the opening of the con-ference on New Trends in Latin American Constitutionalism held at NotreDame Law School in 2013. After briefly recounting the origins of the con-ference, Legarre summarizes some of the key modern challenges in LatinAmerica and the role of constitutionalism in addressing these challenges.Legarre pays particular attention to the rapid growth of income inequalityin the region. He ultimately concludes that some of the major challengesto the region are rooted in a lack of consensus about the common goodas well as a lack of respect for the law. Legarre argues that the solutionto these problems lies in fostering conversations about the proper goals ofLatin American societies and in the political and judicial leaders of LatinAmerica displaying greater fidelity to the principles underlying their respec-tive constitutions